1996
DOI: 10.1177/0265407596134003
|View full text |Cite
|
Sign up to set email alerts
|

Troublesome Relationships: A Part of Human Experience

Abstract: In a study of troublesome relationships, 343 university students and employees were surveyed. Issues addressed were the frequency, nature and precursors of negative relationship experiences. Over half of the respondents (55.7%) reported a very troublesome relationship within the previous 5 years. These were most often close relationships that deteriorated markedly as a result of the experience. Negative relationship involvement was related to insecure styles of attachment. Those with an insecure-avoidant attac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…For instance, persons with secure attachment styles tend to use problem engagement coping and social support, whereas persons with avoidant attachment styles tend to use distancing coping and less support seeking. Ambivalent individuals report more emotion-focused coping, turning to alcohol or drugs (Levitt, Silver, & Franco, 1996), and passive coping.…”
Section: Affective Resolutionmentioning
confidence: 99%
“…For instance, persons with secure attachment styles tend to use problem engagement coping and social support, whereas persons with avoidant attachment styles tend to use distancing coping and less support seeking. Ambivalent individuals report more emotion-focused coping, turning to alcohol or drugs (Levitt, Silver, & Franco, 1996), and passive coping.…”
Section: Affective Resolutionmentioning
confidence: 99%
“…Structural and functional characteristics of the social convoy have been related to both personal and situational influences [Antonucci et al, in press;Levitt, Bustos, Crooks, Levitt, Santos, & Telan, 2000;Levitt, Crooks, Bustos, Levitt, Telan, Santos, Franco, Hodgetts, Milevsky, & Oliva, 2001]. Numerous studies have found convoy support to be associated with psychosocial adjustment; however, convoys do not always function optimally and social relations can sometimes have a negative influence on personal adaptation [Antonucci, 1990[Antonucci, , 2001Levitt, Silver & Franco, 1996].…”
Section: The Convoy Modelmentioning
confidence: 99%
“…Some studies collect data on any perpetrator type, while others focus on intimate or dating partners (Levitt, Silver, & Franco, 1996;Logan, Leukefeld, & Walker, 2000;McCreedy & Dennis, 1996;Pipes & Lebov-Keeler, 1997). A few studies assess lifetime prevalence (Tjaden & Thoennes, 1998), but some limit the time frame to the academic year of the study (Fisher et al, 2002;Mustaine & Tewksbury, 1999) or to five years (e.g., Levitt et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies collect data on any perpetrator type, while others focus on intimate or dating partners (Levitt, Silver, & Franco, 1996;Logan, Leukefeld, & Walker, 2000;McCreedy & Dennis, 1996;Pipes & Lebov-Keeler, 1997). A few studies assess lifetime prevalence (Tjaden & Thoennes, 1998), but some limit the time frame to the academic year of the study (Fisher et al, 2002;Mustaine & Tewksbury, 1999) or to five years (e.g., Levitt et al, 1996). Finally, studies vary dramatically in how stalking is defined, with some studies having victims self-define what constitutes stalking (McCreedy & Dennis, 1996;Mustaine & Tewksbury, 1999), others use a behavior list (e.g., Spitzberg & Rhea, 1999), and still others use legal definitions from the study jurisdiction (e.g., Coleman, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation